2018
DOI: 10.3389/fimmu.2018.02925
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Mapping of Myeloid Cells and Macrophages by Multiplexed Tissue Staining

Abstract: An array of phenotypically diverse myeloid cells and macrophages (MC&M) resides in the tumor microenvironment, requiring multiplexed detection systems for visualization. Here we report an automated, multiplexed staining approach, named PLEXODY, that consists of five MC&M-related fluorescently-tagged antibodies (anti - CD68, - CD163, - CD206, - CD11b, and - CD11c), and three chromogenic antibodies, reactive with high- and low-molecular weight cytokeratins and CD3, highlighting tumor regions, benign glands and T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 60 publications
(65 reference statements)
2
33
0
Order By: Relevance
“…This physical barrier can be TAMs, as they can promote T cell trapping at the border of the tumors by forming long-lasting interactions with CD8 + T cells. 99,100 Tumors defined as altered-immunosuppressed are characterized by poor, although not absent, T cell infiltration due to the presence of an immunosuppressive environment (e.g., myeloid-derived suppressor cells (MDSCs), 101 TAMs, and/or regulatory T cells) within the tumor. Preclinical studies have demonstrated that resistance to immune checkpoint therapy can be circumvented by targeting macrophages with CSF1R inhibitors in colorectal cancer.…”
Section: Tams and Therapymentioning
confidence: 99%
“…This physical barrier can be TAMs, as they can promote T cell trapping at the border of the tumors by forming long-lasting interactions with CD8 + T cells. 99,100 Tumors defined as altered-immunosuppressed are characterized by poor, although not absent, T cell infiltration due to the presence of an immunosuppressive environment (e.g., myeloid-derived suppressor cells (MDSCs), 101 TAMs, and/or regulatory T cells) within the tumor. Preclinical studies have demonstrated that resistance to immune checkpoint therapy can be circumvented by targeting macrophages with CSF1R inhibitors in colorectal cancer.…”
Section: Tams and Therapymentioning
confidence: 99%
“…Compared to undifferentiated cells, expression of human macrophage markers CD11b and CD68 were significantly higher (Fig.5b). In summary, the cells met the criteria of experimental macrophages [21].…”
Section: Humsc-hnf4α Inhibits Lps-stimulated Macrophage Inflammationmentioning
confidence: 92%
“…114,152,153 There are already a growing number of image acquisition platforms in the market that combine image analysis with automated slide scanning to support fluorescence multiplexed staining. These include the Akoya Biosciences Vectra â and Vectra â Polaris TM , 24 TissueGnostics/TissueFAXS, 154 and Leica Biosystems/Aperio FL, 155 all of which can scan slides affixed to whole tissue or tissue microarray slices and provide some level of image analysis. Higher level of multiplexing for multivariate biomarker analysis requires spectral unmixing to separate spectral overlap.…”
Section: Quantitative Digital Image Analysis and Deep Learningmentioning
confidence: 99%